A three-component model of the spinal nerve ramification: Bringing together the human gross anatomy and modern Embryology - Homma, Shunsaku; Shimada, Takako; Wada, Ikuo; Kumaki, Katsuji; Sato, Noboru; Yaginuma, Hiroyuki (Frontiers in Neuroscience, 2023)
Due to its long history, the study of human gross anatomy has not adequately incorporated modern embryological findings; consequently, the current understanding has often been incompatible with recent discoveries from molecular studies. Notably, the traditional epaxial and hypaxial muscle distinction, and their corresponding innervation by the dorsal and ventral rami of the spinal nerve, do not correspond to the primaxial and abaxial muscle distinction, defined by the mesodermal lineages of target tissues. To resolve the disagreement between adult anatomy and embryology, we here propose a novel hypothetical model of spinal nerve ramification. Our model is based on the previously unknown developmental process of the intercostal nerves. Observations of these nerves in the mouse embryos revealed that the intercostal nerves initially had superficial and deep ventral branches, which is contrary to the general perception of a single ventral branch. The initial dual innervation pattern later changes into an adult-like single branch pattern following the retraction of the superficial branch. The modified intercostal nerves consist of the canonical ventral branches and novel branches that run on the muscular surface of the thorax, which sprout from the lateral cutaneous branches. We formulated the embryonic branching pattern into the hypothetical ramification model of the human spinal nerve so that the branching pattern is compatible with the developmental context of the target muscles. In our model, every spinal nerve consists of three components: (1) segmental branches that innervate the primaxial muscles, including the dorsal rami, and short branches and long superficial anterior branches from the ventral rami; (2) plexus-forming intramural branches, the serial homolog of the canonical intercostal nerves, which innervate the abaxial portion of the body wall; and (3) plexus-forming extramural branches, the series of novel branches located outside of the body wall, which innervate the girdle and limb muscles. The selective elaboration or deletion of each component successfully explains the reasoning for the standard morphology and variability of the spinal nerve. Therefore, our model brings a novel understanding of spinal nerve development and valuable information for basic and clinical sciences regarding the diverse branching patterns of the spinal nerve.